Anesthesia and surgery induce age‐dependent changes in postoperative delirium behaviors and microbiota: Developing topics. (7th December 2020) - Liufu, Ning; Liu, Ling; Xie, Zhongcong; Zhang, Yiying
Abstract: Background: Delirium is the most common postoperative complication in senior patients and is associated with accelerated cognitive decline and Alzheimer's disease and related dementia (ADRD). However, the neuropathogenesis of POD remains mostly unknown and no effective medication to prevent or treat POD. Gut microbiota dysbiosis, a condition of microbiota imbalance or maladaptation inside the gut, which could lead to altered immune functions and associated with disorders of POD. Aging and neuroinflammation may also contribute to the neuropathogenesis of POD. However, while all patients may have neuroinflammation, not all patients develop POD. Thus, neuroinflammation alone (single‐factor model of postoperative delirium) is not sufficient to cause POD. Therefore, the objective of the current study was to test the hypothesis that anesthesia/surgery causes age‐dependent gut microbiota dysbiosis, changes in brain IL‐6 level, and mitochondrial function, leading to postoperative delirium‐like behavior in mice. Method: Female 9 or 18 months old mice received abdominal surgery under 1.4% isoflurane for two hours. We employed a battery of natural and learned behavioral tests to determine the delirium‐like behavior, assessed the gut microbiota before and after the anesthesia/surgery by gene pyrosequencing of 16S rRNA, and measured levels of brain IL‐6(ELISA), synaptic marker( Western blot ) and mitochondrial function (Seahorse XFp Extracellular Flux Analyzer) as measures of neuroinflammation and cerebral dysfunction. For intervention, intragastric administration of lactobacillus and probiotic were used to mitigate the anesthesia/surgery‐induced above changes. Result: Anesthesia/surgery caused different alterations in gut microbiota, including change rate of reduction in the levels of gut lactobacillus, between the 18 and 9 months old mice. The anesthesia/surgery induced greater postoperative delirium‐like behavior, increased brain IL‐6 levels, decreased PSD‐95 and synaptophysin levels, and mitochondrial dysfunction in 18 than 9 months old mice. Treatments with lactobacillus and probiotic mitigated the anesthesia/surgery‐induced changes. Conclusion: We demonstrated that anesthesia/surgery induces age‐dependent changes in the gut microbiota(reduction in lactobacillus), increases brain levels of IL‐6, decreases levels of synaptic marker, and reduces mitochondrial function while also promoting the development of postoperative delirium‐like behaviors in the mice. Treatment with lactobacillus or probiotic mitigated these detrimental effects, strongly suggesting that abnormalities in the gut microbiota contribute to the development of postoperative delirium.